Modelling and implementing a bilingual improved management system for research grants - Farooqi, Norah; Baz, Abdullah (International Journal of Engineering and Technology, 2018)
Research is a vital process in academic and industrial communities requiring a lengthy process involving activities from different parties, including principal investigators, research teams, funding agencies, reviewers, and administrators. Moreover, successful research requires efficient management of several resources, including human and financial resources, which can be a challenging task to ensure positive out-comes of resulting research projects. Therefore, many funding agencies around the world that attempt to regulate this process through one or more information systems. However, according to existing literature, there is a gap between the existing systems and required functionalities. This paper describes a new design and implementation of a management system at UQU to encompass all research activities from Saudi funding agencies. The developed system was tested through two rounds of proposal submissions during two academic years. The results demonstrate improvements in the proposed system over existing products regarding functionality and integration.